Developing thinking around mental health science: the example of intrusive, emotional mental imagery after psychological trauma. Issue 5 (2nd September 2020) - Singh, Laura; Espinosa, Lisa; Ji, Julie L.; Moulds, Michelle L.; Holmes, Emily A.
ABSTRACT: Introduction: One route to advancing psychological treatments is to harness mental health science, a multidisciplinary approach including individuals with lived experience and end users (e.g., Holmes, E. A., Craske, M. G., & Graybiel, A. M. (2014). Psychological treatments: A call for mental-health science. Nature, 511 (7509), 287–289. doi:10.1038/511287a ). While early days, we here illustrate a line of research explored by our group—intrusive imagery-based memories after trauma. Method/Results: We illustrate three possible approaches through which mental health science may stimulate thinking around psychological treatment innovation. First, focusing on single/specific target symptoms rather than full, multifaceted psychiatric diagnoses (e.g., intrusive trauma memories rather than all of posttraumatic stress disorder). Second, investigating mechanisms that can be modified in treatment (treatment mechanisms), rather than those which cannot (e.g., processes only linked to aetiology). Finally, exploring novel ways of delivering psychological treatment (peer-/self-administration), given the prevalence of mental health problems globally, and the corresponding need for effective interventions that can be delivered at scale and remotely for example at times of crisis (e.g., current COVID-19 pandemic). Conclusions: These three approaches suggest options for potential innovative avenues through which mental health science may be harnessed to recouple basic and applied research and transform treatment development.